2009
DOI: 10.1371/journal.pone.0005083
|View full text |Cite
|
Sign up to set email alerts
|

Skin Blood Perfusion and Oxygenation Colour Affect Perceived Human Health

Abstract: Skin blood perfusion and oxygenation depends upon cardiovascular, hormonal and circulatory health in humans and provides socio-sexual signals of underlying physiology, dominance and reproductive status in some primates. We allowed participants to manipulate colour calibrated facial photographs along empirically-measured oxygenated and deoxygenated blood colour axes both separately and simultaneously, to optimise healthy appearance. Participants increased skin blood colour, particularly oxygenated, above basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
209
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(232 citation statements)
references
References 54 publications
(77 reference statements)
18
209
1
4
Order By: Relevance
“…The significant Image type x Quality x Color condition interaction suggests that higher scores are awarded to high quality individuals compared with low quality individuals when presented in the color condition than in monochrome, but only for the skin images. Our results are consistent with recent findings that skin color and the distribution of skin coloration are important in judgements of mate quality (Fink et al 2001(Fink et al , 2006Jones et al 2004a, b;Stephen et al 2009). Color information is not the only cue to quality, however, since high quality individuals received higher scores than low quality individuals, even when judged in monochrome, in both face and skin image presentations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The significant Image type x Quality x Color condition interaction suggests that higher scores are awarded to high quality individuals compared with low quality individuals when presented in the color condition than in monochrome, but only for the skin images. Our results are consistent with recent findings that skin color and the distribution of skin coloration are important in judgements of mate quality (Fink et al 2001(Fink et al , 2006Jones et al 2004a, b;Stephen et al 2009). Color information is not the only cue to quality, however, since high quality individuals received higher scores than low quality individuals, even when judged in monochrome, in both face and skin image presentations.…”
Section: Discussionsupporting
confidence: 93%
“…It has been argued, for example, that men prefer women with relatively pale skin as this is associated with youth (van den Berghe and Frost 1986, but see Fink et al 2001) and that redness of cheeks could be a signal of health (Zahavi and Zahavi 1997). Indeed, skin redness has since been shown to be associated with both perceived health and attractiveness (Stephen et al 2009(Stephen et al , 2012 in facial rating studies. Furthermore, relating color attributes to attractiveness ratings, Fink et al (2001) found that attractiveness was negatively correlated with variability in blue color space in women's faces, but was also predicted by homogeneity of contrast, suggesting that both color and textural cues influence judgments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…yellowness or redness axis in isolation), other 85 research has linked health perception to naturally occurring skin pigments: for skin redness, 86 participants increased the amount of oxygenated blood colour more than deoxygenated blood 87 colour, to maximise the appearance of health in faces (Stephen et al, 2009b been shown to increase T-lymphocyte counts in healthy adults (Alexander et al, 1985) and 115 has beneficial effects for thymus gland growth in children (Seifter, et al, 1981 The two groups did not differ on gender, age, BMI, or exercise behaviour. Skin colour was 157 measured on the forearm using spectrophotometry (for details see Whitehead et al, 2012b).…”
mentioning
confidence: 99%
“…Some cosmetic products seem specifically tailored to modifying these perceptions. For example, blushers typically add redness to the face, a colouration tied to circulatory health and a healthy appearance (Stephen, Coetzee, Law-Smith, & Perrett, 2009). Indeed, an application of cosmetics has positive effects on health perceptions (Mulhern, Fieldman, Hussey, Lévêque, & Pineau, 2003).…”
mentioning
confidence: 99%